Side Effects of Nitrification Inhibitors on Non Target Microbial Processes in Soils - Ferisman Tindaon; Gero Benckiser; Carl Gottlieb Ottow (JOURNAL OF TROPICAL SOILS, 2011)
Agricultural chemicals have been used extensively in modern agriculture and toxicological studies suggest a great potential for inducing undesirable effects on non target organisms. A model experiment was conducted in order to determine side effects of three nitrification inhibitors (NIs, 3,4dimethylpyrazolephosphate = DMPP, 4-Chlormethylpyrazole phosphate = ClMPP and dicyandiamide = DCD) on non target microbial processes in soils. Side effects and dose response curve of three NIs were quantified under laboratory conditions using silty clay, loam anda sandy soils. Dehydrogenase, dimethylsulfoxide reductase as well as nitrogenase activity (NA) and potential denitrification capacity were measured as common and specific non target microbial processes. The influence of 5-1000 times the base concentration, dose response curves were examined, and no observable effect level = NOEL, as well as effective dose ED10 and ED50 (10% and 50% inhibition) were calculated. The NOEL for microbial non target processes were about 30–70 times higher than base concentration in all investigated soils. The potential denitrification capacity revealed to be the most sensitive parameter. ClMPP exhibited the strongest influence on the non target microbial processes in the three soils. The NOEL, ED10 and ED50 values were higher in clay than in loamy or sandy soil. The NIs was the most effective in sandy soils.Keywords: microbial non target processes, nitrification inhibitors, soil enzymes